2006
DOI: 10.4049/jimmunol.177.6.4055
|View full text |Cite
|
Sign up to set email alerts
|

Distinct In Vivo Roles of Colony-Stimulating Factor-1 Isoforms in Renal Inflammation

Abstract: CSF-1, the major regulator of macrophage (Mφ) development, has three biologically active isoforms: a membrane-spanning, cell surface glycoprotein, a secreted glycoprotein, and a secreted proteoglycan. We hypothesized that there are shared and unique roles of individual CSF-1 isoforms during renal inflammation. To test this, we evaluated transgenic mice only expressing the cell surface or precursors of the secreted CSF-1 isoforms for Mφ accumulation, activation, and Mφ-mediated tubular epithelial cell (TEC) apo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 45 publications
1
38
0
Order By: Relevance
“…The MRL-Fas lpr kidney may be self-destructive. Because renal TECs are a rich source of CSF-1 during inflammation, 20 CSF-1 originating from the kidney may, in part, account for the rise in circulating CSF-1 that drives Mø Figure 7. CSF-1 is elevated in urine and serum of patients with lupus nephritis and correlates with disease activity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The MRL-Fas lpr kidney may be self-destructive. Because renal TECs are a rich source of CSF-1 during inflammation, 20 CSF-1 originating from the kidney may, in part, account for the rise in circulating CSF-1 that drives Mø Figure 7. CSF-1 is elevated in urine and serum of patients with lupus nephritis and correlates with disease activity.…”
Section: Discussionmentioning
confidence: 99%
“…41 To identify ␤-galactosidase encoded by lacZ (CSF-1 expression), we treated frozen kidney sections as described previously. 20 …”
Section: Mouse Tissuementioning
confidence: 99%
See 1 more Smart Citation
“…It is interesting that engagement of the CSF-1 receptor is required for the differentiation and survival of myeloid DC, 44 and constitutive expression of CSF-1 (i.e., M-CSF, a major chemoattractant and growth factor for mononuclear phagocytes 45 ) by renal epithelial cells seems to be more prominent in the medulla than in the cortex at steady state. 46,47 Whether this alone explains the heterogeneity of rDC is unclear. More likely, other differentially expressed trophic ligands (thymic stromal lymphopoietin-like factors that may be elaborated by renal epithelial cells or interstitial stromal cell populations 48,49 ) and extracellular matrices within the kidney also contribute to the specification of rDC.…”
Section: Origins and Migration Of Rdc At Steady Statementioning
confidence: 99%
“…Our previous studies indicated that the individual csCSF-1 and the spCSF-1 and sgCSF-1 isoforms have distinct functions in nonautoimmune incited renal inflammation on the basis of stability, availability, and the large (approximately 18,000 M r ) chondroitin sulfate chain (ChS) on spCSF-1, but not sgCSF-1. 13 To design a CSF-1 targeted therapeutic approach for lupus nephritis, it is essential to decipher whether blocking CSF-1 expression in the circulation and/or Figure 1. spCSF-1, but not csCSF-1, contributes to the increase in serum CSF-1, and both are upregulated in the kidney with advancing disease in MRL-Fas lpr mice.…”
mentioning
confidence: 99%